2016
DOI: 10.1093/femspd/ftw056
|View full text |Cite
|
Sign up to set email alerts
|

Penetration barrier contributes to bacterial biofilm-associated resistance against only select antibiotics, and exhibits genus-, strain- and antibiotic-specific differences

Abstract: Bacterial biofilms are implicated in a wide range of implant-based and chronic infections. These infections are often associated with adverse therapeutic outcomes, owing to the decreased antibiotic susceptibility of biofilms compared with their planktonic counterparts. This altered biofilm susceptibility has been attributed to multiple factors, including a reduced antibiotic penetration. Although several studies have addressed the role of penetration barrier in biofilm-associated drug resistance, it remains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 22 publications
7
75
0
Order By: Relevance
“…4D). Since the biofilm matrix of E. coli is known to impede ␤-lactam penetration significantly (48), this change correlates well with the significant decrease in Amp susceptibility in 0.85% NaCl among attached cells (77.4% decrease between 3-and 4-h biofilms; P Ͻ 0.0001, two-way ANOVA adjusted by Tukey test) (Fig. 1A).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…4D). Since the biofilm matrix of E. coli is known to impede ␤-lactam penetration significantly (48), this change correlates well with the significant decrease in Amp susceptibility in 0.85% NaCl among attached cells (77.4% decrease between 3-and 4-h biofilms; P Ͻ 0.0001, two-way ANOVA adjusted by Tukey test) (Fig. 1A).…”
Section: Resultssupporting
confidence: 53%
“…Collectively, these results indicate that cellulose and curli may influence the antibiotic susceptibility of surfaceattached E. coli cells. Unlike ␤-lactam, the E. coli biofilm matrix cannot prevent fluoroquinolone penetration effectively (48), which explains why the susceptibility of biofilm cells to Ofx (fluoroquinolone family) did not show significant change at the same time point (P ϭ 0.9257, two-way ANOVA adjusted by Tukey test) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This antibiotic acts by binding to the D-Ala-D-ala residues of the membrane bound cell wall precursor, lipid II, preventing its incorporation and stalling active peptidoglycan synthesis 27 . Importantly, some studies have indicated that vancomycin penetration is impeded into biofilms 17 . US-PCCA potentiated vancomycin killing of biofilm-associated cells by 93% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, cells within the biofilm are far more resistant to a wide range of stressors, including cleaning chemicals and sanitizers, than their free‐living counterparts . This resistance results from a number of factors associated with living within a biofilm, including physical and chemical binding of antimicrobial compounds by EPS, modifications in EPS composition and quantity, imposition of biofilm‐specific mode of growth, or physical protection / engulfment of the sensitive species by the tolerant ones in multispecies biofilm . Moreover, the resistance of cells within a biofilm can also depend on the hydrophobic protective layer of EPS structures, for instance, specified by a small hydrophobic protein called BslA in B. subtilis …”
Section: Biofilm‐forming Bacteria Contaminate Dairy Food and Deteriormentioning
confidence: 99%